2011
DOI: 10.2136/sssaj2010.0269
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Availability as Affected by the Long-Term Application of Phosphorus Fertilizer and Organic Amendments

Abstract: Micronucrient availability is important to crop production and can be affected by long-term application of P and organic amendments. This study was condutted to determine the effects ofthe long-term application of different sources and rates of P application on extracrable [DTPA-sorbitol (diethylenetriamine-pentaacetic acid and sorbitol] micronutrients. Soil extractable and total micronutrients (B, Cu, Fe, Mn, Mo, and Zn), pH, and organic matter content were determined from sites across Oklahoma that had recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Crop residue is returning not only can increase crop yields, but it also can enhance soils' resistance to wind and water erosion [6,7]. Animal manures, such as pig manure with ample N, P and K, are valuable resources to supply the needed plant nutrients and organic matters [2,4,5,8,9]. Therefore, rice straw and fresh pig manure are commonly used as organic amendments in the red soil region of China.…”
Section: Introductionmentioning
confidence: 99%
“…Crop residue is returning not only can increase crop yields, but it also can enhance soils' resistance to wind and water erosion [6,7]. Animal manures, such as pig manure with ample N, P and K, are valuable resources to supply the needed plant nutrients and organic matters [2,4,5,8,9]. Therefore, rice straw and fresh pig manure are commonly used as organic amendments in the red soil region of China.…”
Section: Introductionmentioning
confidence: 99%
“…Richards et al (2011) found that the application of fertilizers for several years significantly increased organic matter content and the concentrations of available forms of Fe, Cu, Mn, Zn and Mo in the soil and also find significant correlations between total amounts of micronutrients applied through organic fertilizer and available forms of those micronutrients in the soil. As organic fertilizer did not impact soil pH, which greatly affects the availability of micronutrients, the increase of micronutrient concentrations is probably a result of the interaction between metal ions and various organic acids created during the mineralization of applied organic matter, and formation of chelated complexes (Leita et al, impact on soil fertility and yield 1999).…”
Section: Resultsmentioning
confidence: 88%
“…Eghball et al (1997) remark that in comparison to farmyard manure, a considerable part of readily degradable organic C and N in composts is lost during composting, while remaining C and N are found in more stable forms which are more resistant to mineralization and have weaker affinity to metal ions in the creation of chelated complexes. Besides this, by applying farmyard manure significantly more organic C was incorporated into the soil than was the case with compost (mushroom compost and vermicompost) treatments (Table 2), which could also have led to farmyard manure having a higher impact on available micronutrient concentrations than composts (Richards et al, 2011). The differences between the two mulching methods could have arisen from higher soil temperatures, more intensive mineralization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorus concentrations in runoff were significantly correlated with K ( r = 0.54) and all of the other metals in runoff, except for Zn (Table 3). This is understandable because poultry litter and cattle manure contain relatively high concentrations of P and metals, and hence manure additions would increase the availability of all metals (He et al, 2009; Richards et al, 2011). It should be mentioned that the current research was originally planned to evaluate the effects of buffers and grazing management on P runoff, and a manuscript concerning those results is in preparation.…”
Section: Resultsmentioning
confidence: 99%